Etnomatematika: Eksplorasi Konsep Matematika pada Gerobak Sapi Yogyakarta - Arvianto, Ilham Rais; Fadila, Abi; Nurcahyo, Adi; Farizqi, Muhammad Luthfi (Edumatica : Jurnal Pendidikan Matematika, 2025)
Yogyakarta's ox carts, though culturally significant and increasingly rare, have not yet been explored as sources of mathematical concepts. This study addresses the urgency of preserving and utilizing these traditional artefacts as contextual tools for mathematics education. This ethnographic research aims to identify and describe mathematical concepts—geometry, arithmetic, algebra, and statistics—embedded in various parts of the Yogyakarta ox cart. Data were collected through interviews and observations, with the subject being an ox cart craftsman and the object being the mathematical concepts found in the cart’s section. Data analysis followed the Miles and Huberman model. The findings reveal four major mathematical concepts: (1) Geometry, including rectangles, trapezoids, rhombuses, triangles, reflections, translations, rotations, parallel and intersecting lines, angles, and tessellations; (2) Arithmetic, involving arithmetic sequences and division operations; (3) Algebra, in the form of variable terms; and (4) Statistics, represented by the mode topic. These findings contribute to the field of ethnomathematics by introducing a new cultural context and supporting the development of mathematical materials based on local wisdom, making learning more realistic. Integrating local heritage into mathematics instruction can foster a deeper understanding, increased student engagement, and a greater appreciation for cultural diversity, offering meaningful and realistic learning experiences.